If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(a + b) = f (a * 3 + b * 3) = f (3a + 3b) = f Solving 3a + 3b = f Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. 3a + 3b + -3b = -3b + f Combine like terms: 3b + -3b = 0 3a + 0 = -3b + f 3a = -3b + f Divide each side by '3'. a = -1b + 0.3333333333f Simplifying a = -1b + 0.3333333333f
| 35x^2-9x-2=0 | | (-6x+7)=(19x-1) | | 9y+4-7y=124 | | -10(x-1)=-10x | | 0=4x^2+39x-10 | | -5b+6(1-b)=83 | | 2x^4-x^3-9x^2+13x-4=0 | | y-5=7(x-6) | | 2x^4-x^3-9x^2+13-4=0 | | b-a=d | | p^3-3p+2=0 | | 18y+3y=6 | | s(4+p)=m | | X+3.2=7.5 | | 5(+4)=18-9 | | 3(4-6k)+1=-131 | | 3y+18y=6 | | 36x^2-48x+16=1 | | -5q-2(1-q)=-6q | | -2-1=-x-3 | | 3x+3x+15+2x+5=180 | | 6m+3=3m+3 | | 45b+2=-15b+3 | | h+9.1=5.3 | | 3+6=m | | 14x+7+20x+5=90 | | -3(6k+7)+6=93 | | 3(x+9)-2x+7=3(5x-8)-13x-7 | | 2x^2+8x+2y^2=0 | | 2(a-5-3)-5=3 | | 20+(-8x)-18=x | | -2x^2-3x+360=0 |